2005
DOI: 10.1002/adsc.200505145
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Modular Syntheses of Fluorous Secondary Phosphines and Selected Derivatives

Abstract: Reactions of the fluorous primary phosphines R fn (CH 2 ) 2 PH 2 [R fn ¼ (CF 2 ) n À 1 CF 3 ; n¼ 6, 8, 10] and R fn' CH ¼ CH 2 [(n' ¼ 6, 8, 10) (CH 2 ) 2 ] 2 PCl or R f8 (CH 2 ) 2 PCl 2 , which are characterized in situ. The CF 3 C 6 F 11 /toluene partition coefficients of 4 -9 increase with the number and lengths of the R fn segments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In previous studies, we have reported a variety of syntheses of fluorous aliphatic primary, secondary, and tertiary phosphines bearing R fn A C H T U N G T R E N N U N G (CH 2 ) m substituents, [7][8][9][10] and related aromatic species. [7,11] Many of the routes to the aliphatic systems are modular in nature, allowing each ponytail to be individually controlled.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we have reported a variety of syntheses of fluorous aliphatic primary, secondary, and tertiary phosphines bearing R fn A C H T U N G T R E N N U N G (CH 2 ) m substituents, [7][8][9][10] and related aromatic species. [7,11] Many of the routes to the aliphatic systems are modular in nature, allowing each ponytail to be individually controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Their highly efficient addition reactions to alkenes have been achieved with transition metal catalysts [22][23][24]. A radical reaction involving phosphorus-centered radicals generated in situ is a classical method for P-C bond formation [25][26][27][28][29][30]; however, the use of primary phosphines and phosphine oxides in a radical reaction is relatively rare compared to that of secondary phosphines and phosphine oxides [31][32][33][34][35][36][37][38]. The stereochemistry on a phosphorus atom has not received much attention, despite the fact that the introduction of at least three different substituents to the phosphorus atom gives rise to the stereogenic center on the phosphorus atom.…”
Section: Introductionmentioning
confidence: 99%